1999
DOI: 10.1177/0143034399202003
|View full text |Cite
|
Sign up to set email alerts
|

Sudden Death of a Classmate and Friend

Abstract: Following the accidental death of an 8th grade student, 26 classmates answered questionnairies after one and nine months. In addition, a qualitative interview was carried out with half the class and six close friends after one month. There was a strong positive endorsement of the school's response following the death. The students valued the opportunity to talk and take part in ritual activities. However, close friends from outside the dead boy's class went largely unnoticed, and assistance based on a better u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Recent empirical work demonstrates bereaved children's need to talk. For example, Dyregrov, Bie Wikander, & Vigerust (1999) found that children themselves reported a good response by teachers to one pupil's death, although one child stated, 'we should have talked a little more about him [pupil]'. In the present study we found that students reported mature responses and impeccable behaviour following a bereavement indicate a high level of empathy amongst young children; a similar level of sensitivity and empathy towards those who are bereaved has also been found in American children (Balk, 1989).…”
Section: The Impact On Teachers Of Bereaved Studentsmentioning
confidence: 99%
“…Recent empirical work demonstrates bereaved children's need to talk. For example, Dyregrov, Bie Wikander, & Vigerust (1999) found that children themselves reported a good response by teachers to one pupil's death, although one child stated, 'we should have talked a little more about him [pupil]'. In the present study we found that students reported mature responses and impeccable behaviour following a bereavement indicate a high level of empathy amongst young children; a similar level of sensitivity and empathy towards those who are bereaved has also been found in American children (Balk, 1989).…”
Section: The Impact On Teachers Of Bereaved Studentsmentioning
confidence: 99%